Design and validation of a control sheet for arterial hypertension (Boletín Semillero de Investigación en Familia, 2023)
Introduction: arterial hypertension is a highly prevalent disease. The Mexican Institute of Social Security makes use of the electronic sheet for monitoring and control; however, it has some drawbacks, so making a proposal to improve this tool will help the experience so that care is safe, effective, patient-centered, timely, and equitable. Objectives: design and validate a new control sheet for patients with hypertension based on the Family Medicine Information System platform. Materials and methods: with variables related to the control and follow-up of the patient with hypertension, a control sheet was integrated. After undergoing expert judgment, the validity of the instrument was determined and its reliability with operative physicians was assessed. Results: the electronic sheet was designed and evaluated by the experts. A good concordance of 0.766 (p = 0.008) was found with the Kendall's W test and a good reliability of 0.758 was found by means of the Cronbach's alpha test performed by the physicians in family medicine units. Conclusion: this proposal for an electronic sheet for the control of arterial hypertension meets acceptable validity and reliability.
Keywords: Hypertension; design; validation; medicine; familiar.